The Development of Human Resources in Information Technology in Vietnam from 2006 to 2020 - Hoang Hai Ha; Bui Thi Bich Thuan, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
This article aims to shed light on the development of Vietnam's information technology human resources between 2006 and 2020 by analyzing the guidelines and policies set by the Communist Party and the Government of Vietnam, as well as their training activities, talent attraction, compensation and international cooperation policies. Information technology (IT) and IT human resources play a crucial role in Vietnam's socio-economic development, particularly in the rapidly evolving context of the information and digital revolutions. Since 2006, as Vietnam entered a phase of industrialization and modernization tied to the growth of a knowledge-based economy, the Party and the government have increasingly recognized the importance of applying and developing IT across all fields. In this regard, IT human resources are key to promoting the role of information technology in the country’s development strategy. Recently, Vietnam has emerged as a significant player in the global IT industry but workforce shortages have challenged the country’s long-term objective of becoming a tech hub in Southeast Asia.Received 10th March 2024; Revised 20th March 2024; Accepted 16th April 2024